Binding characteristics of systemic glucocorticoids with the SARS-CoV-2 spike glycoprotein: in-silico evaluation - Khmil, N. V.; Boiechko-Nemovcha, A. O.; Kolesnikov, V. G. (My University, 2024)
The aim of the study was to evaluate the binding characteristics of systemic glucocorticoids with the SARS-CoV-2 S protein and to elucidate the topological features of non-covalent ligandprotein complexes.
Keywords: glucocorticoids; ligandprotein; protein targets